2004
DOI: 10.1191/0269216304pm892oa
|View full text |Cite
|
Sign up to set email alerts
|

Equity of access to adult hospice inpatient care within north-west England

Abstract: There is a growing debate about the question of equity of access to hospice and palliative care services. Even countries with relatively well developed palliative care systems are considered to have problems of access and inequity of provision. Despite these concerns, we still lack a relevant evidence base to serve as a guide to action. We present an analysis of access to adult hospice inpatient provision in the north-west region of England that employs Geographical Information Systems (GIS). Measures of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Further analysis and understanding of the experience of the dying poor and their families is required, with a focused commitment to both identify and evaluate interventions aimed at modifying and eliminating disparity. Hospice enrolment reduced emergency room visits for low SE groups (Bergman et Longer drive times to palliative care services for patients in SE deprived areas (Wood et al 2004) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further analysis and understanding of the experience of the dying poor and their families is required, with a focused commitment to both identify and evaluate interventions aimed at modifying and eliminating disparity. Hospice enrolment reduced emergency room visits for low SE groups (Bergman et Longer drive times to palliative care services for patients in SE deprived areas (Wood et al 2004) …”
Section: Resultsmentioning
confidence: 99%
“…The ad-hoc nature in which palliative care services have developed worldwide has supported disparities in access based on geographical location [41,42] A meta-analysis by Higginson and Constatini [36] found that the distribution of palliative care services in Europe was inequitable and that services were not necessarily located in areas based on greatest need . Poor Indigenous groups in rural and remote areas in Australia, held very strong cultural and spiritual preferences for home deaths, but were least likely to achieve this aim, due to a lack of local services [25].…”
Section: Geographical Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a relatively small number of empirical studies have been conducted on administrativerelated issues. Since the palliative care movement began in England, several studies have examined funding and access issues in the United Kingdom (cf., Matthew, Cowley, Bliss, & Thistlewood, 2003;Sims, 1995;Wood, Clark, & Gatrell, 2004). A couple of studies have examined similar funding and utilization issues in the United States (cf., Han et al, 2006;Huskamp, Buntin, Wang, & Newhouse, 2001).…”
mentioning
confidence: 99%